Consecutive Vibrational Redistribution and Predissociation Processes in s-Tetrazine–Argon Van Der Waals Complexes. Issue 3 (1983) - Ramaekers, J. J. F.; Krijnen, L. B.; Lips, H. J.; Langelaar, J.; Rettschnick, R. P. H.
Abstract : s -Tetrazine argon complexesT − Ar n ( n = 1, 2) are formed in a supersonic expansion of argon seeded with s -tetrazine. The expansion was conducted through a nozzle of 50 or 100 μm with an argon stagnation pressure between 1 and 1.5 bar. From spectrally resolved measurements it is clear that vibrational redistribution processes as well as vibrational predissociation processes take place after SVL excitation within the complex. From rise and decay time experiments it can be concluded, that after excitation of the 6 a 1 complex level, the above mentioned processes are consecutive and not parallel. It appears that the out of plane mode 16 a couples with the Van der Waals stretching mode. The predissociation rate of the 16 a 2 complex is observed to be 2.3 × 10 9 s −1 .